The influence of principal leadership and teachers’ professionalism on the effectiveness of school-based management at state elementary schools of keluang district - Sadiman Sadiman; Yasir Arafat; Mulyadi Mulyadi (Journal of Educational and Learning Studies, 2021)
This study aimed to analyze the influence of principal leadership and teachers’ professionalism on the effectiveness of school-based management at State Elementary Schools ofKeluang District. The data of this study were collected by distributing questionnaires to respondents. Then they were analyzed by using multiple regression analysis through the t test, F test, and determination coefficient test. Population of the study was 308 Public Elementary School teachers ofKeluang District. The sampling technique used was probability sampling. Thus, the sample in the study was 174 teachers of Elementary Schools ofKeluang District. The results of the study found that: 1) there was a significant influence of principal leadership on the effectiveness of school-based management at state elementary schools ofKeluang District; 2) there was a significant effect of teacher professionalism on the effectiveness of school-based management at state Elementary Schools ofKeluang District; 3) there was a significant influence of principal leadership and teacher professionalism simultaneously on the effectiveness of school-based management at state Elementary Schools ofKeluang District.